Magnetoelastic stresses in rare-earth thin films and superlattices - Arnaudas, J. I.; Dumesnil, K.; Dufour, C.; Wells, M. R.; Ward, R. C. C.; Moral, A. del; Benito, L.; Fuente, C. de la; Ciria, M.; Mougin, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We report on the study of the magnetoelastic behavior of some rare-earth based thin films and superlattices (SL`s). Magnetoelastic stress (MS) measurements (by using a cantilever capacitive technique) within a wide range of temperatures (10-300 K) and magnetic fields (up to 12 T) have been performed. We derive expressions relating the cantilever curvatures and the magnetoelastic stresses in anisotropic thin films and SL`s (for cubic symmetry) deposited onto crystalline substrates. The magnetoelastic energy associated to the interfaces and the epitaxial stress dependence of the volume MS has been investigated by studying the basal plane MS in Hon/Lu15 and in Ho10/Ym SL`s: we obtain interface MS even higher than the volume ones and the effect in bulk`s MS of the epitaxial strain is large. In Dy/Y and Er/Lu SL’s we also deduce the MS contributions but, for Er/Lu, incomplete saturation leads to inconclusive results. Although the latter case also happens in Ho/Tm SL`s, MS clearly shows anisotropy competition. In TbFe2 (t) / YFe2(1000 Å) (300 Å < t < 1300 Å) epitaxial bilayers, we determine all the MS allowed by the symmetry and show that epitaxial stress strongly modifies the tetragonal MS. The thermal dependence of MS parameters is also analysed.